Implementation of the Teacher in Educational Management Literacy at Elementary School - Ridwan Ridwan (LPPM Universitas Bumigora Mataram, 2023)
School of literacy movement has the goal of familiarizing and motivating students want to read and write in order to foster characters. Literacy Movement is a participatory effort or activity involving school members (students, teachers, school principals, education staff, school supervisors. Need for proper management in literacy learning. This study aims to answer the question how to manage educational literacy in elementary school through four aspects of activities namely planning, organizing, implementing and evaluating. This study used a qualitative approach with a descriptive research type. This research used in-depth interviews. The data analyzed in this study were in the form of narrative transcripts produced through interview and documentation techniques. The stages the analysis is data reduction, data presentation and data verification. The results of this study indicate that 85% of several elementary schools in Langsa City apply planning in the educational literacy management program carried out by the school is to set goals, make short term plans as the main goal from the learning literacy management program is used so that it is effective and efficient.